Uma ontologia sobre licitações aplicada na elicitação de requisitos de portais de transferência municipal - Bernardi, Tainara Lucateli (2017)
In order for information technology professionals to develop systems that contribute to government management, they need to understand the conceptual basis involved in the complex domains of municipal governments. The lack of standardization of concepts has made it difficult to elicit requirements for the development of new software. Due to this reality, the modeling of a domain ontology on bids and administrative contracts is presented, along with the development of a tool (ReqOnto) that allows the application of this ontology in the elicitation activity. Through the experiment using the ontology in defining requirements for a new portal of municipal transparency, it is confirmed that this process presents an alternative way for the professionals of the field to understand the context of the new system, thus enabling the definition of requirements that meet the needs of public management and the mandates established by Brazilian legislation.